Management of Psoriasis by Family Physicians: Referral Algorithm and Shared Management with Dermatology - Torres, Tiago (2021)
Introduction: The implementation of models capable of improving referral quality, limiting the growth of waiting lists in hospitals, and ensuring the best possible treatment and follow-up of the psoriatic patient is of the utmost importance.Material and Methods: A panel of Family Physicians and Dermatologists discussed and created a simple and effective algorithm of referral for patients with psoriasis.Results: The proposed algorithm starts when the Family Physician suspects of psoriasis. In case of diagnostic doubt, the patient should be referred to Dermatology. In case of a confirmed diagnosis, the Family Physician should assess the patient’s severity and responder profile, evaluate comorbidities and assess the presence of psoriatic arthritis. If psoriasis is mild, topical treatments should be initiated, and if there is no clinical improvement or worsening of the disease, the patient should be referred to Dermatology. If psoriasis is moderate to severe, is located in high impact locations, or in pediatric age, the patient should be referred to Dermatology. In order to enable shared management in terms of follow-up and treatment of these patients, it is critical that the Family Physician has the necessary knowledge regarding the systemic treatments used in psoriasis and their side effects.Discussion and Conclusion: Only a shared management of the psoriatic patient can allow for the best treatment and follow-up of these patients, a more rational use of available medical resources, thus giving the patient the best possible quality of life.